Enhanced expression of synoviolin in peripheral blood from obese/overweight donors - Fujita, Hidetoshi (Exp Ther Med, 2020)
Obesity is currently a major medical and societal issue. Synoviolin (SYVN1) is an E3 ubiquitin ligase involved in endoplasmic reticulum (ER) stress. Overexpression of Syvn1 has been found in genetically obese mice (ob/ob and db/db), and treatment with a Syvn1 inhibitor suppresses weight gain in some mouse models (C57BL/6J and db/db). However, SYVN1 expression in humans has not yet been elucidated. In the present study, 35 human volunteers were analyzed, and the expression level of SYVN1 mRNA in peripheral blood mononuclear cells (PBMCs) was detected using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis. Expression of SYVN1 mRNA was significantly increased in PBMCs from volunteers with a BMI ≥25.0, compared with volunteers with a BMI <25.0. In addition, PCR array and RT-qPCR of ER stress-responsive genes revealed that the expression of activating transcription factor 6 (ATF6), which plays an important role in the transcriptional activation of SYVN1, was increased in PBMCs from volunteers with a BMI ≥25.0. These results suggest that the ATF6-SYVN1 axis might be an important pathway in the progression of obesity.